PERJALANAN HIDUP TOKOH DALAM PUISI THE RAVEN KARYA EDGAR ALLAN POE - Sidik, Fajar (Apollo Project: Jurnal Ilmiah Program Studi Sastra Inggris, 2022)
The title of this research is Perjalanan Hidup Tokoh dalam Puisi The Raven karya Edgar Allan Poe. This research explains the description of the main character and the way of the main character live his life using imagery and figurative language. The Descriptive and Qualitative use on this research by taking all the data's poem in the form of lines and stanzas. The approach in this study uses the Objective Approach, because this research focuses on the literature itself. The result of this research show the main character as a coward, hypophrenia, and unstable. The main character in The Raven lives a life full of struggles, sorrows and sacrifices.